Fabrication of nanostructured anodized aluminum oxide (AAO) on Si-Al substrate for electronic applications - Nur Hafiza, Mohd Najib
The growth of anodized aluminum oxide (AAO) film in anodizing process has been studied. The anodizing process was done in oxalic acid. The purpose of choosing oxalic acid as the electrolyte is to create AAO with a medium pore nanometer diameter. This study was performed to determine optimum parameters of anodizing process in order to develop AAO film for various applications in electronic field. This study focussed on the influence of anodizing parameters such as anodizing voltage, electrolyte temperature and electrolyte concentration to the growth of AAO film. The anodizing voltage was varied from 40V to 55V, temperature was controlled from 10°C to 25°C and the concentration was varied from 0.1M to 0.7M. The dielectric properties also studied via impedance spectroscopy. The growth of AAO was studied through the composition, morphology, and cross section analysis. Characterization for physical and chemical properties is observed by using Scanning Electron Microscopy (SEM) and X-Ray Diffraction (XRD) techniques. The results show that the formation of AAO film was strictly influenced by the anodizing conditions. The average pore diameter 43.99nm measured was the highest at 40V. Self ordering and great pore structures occurred whenever the voltage was 45V Meanwhile, the average pore diameter of AAO film at different temperature was the largest at 25°C around 38.89nm. For varied concentration, the highest value of pore diameter observed in 0.3M which is 39.62nm. The most highly ordered structure of AAO pore was formed at 45V at temperature 20°C and 0.7M of concentration. The kinetic reaction for AAO film was expressed in term of percentage of mass changes and thickness of the film. The higher anodizing voltage, the higher the percentage of mass change which is 1.27% at 55V. At 25°C, the thickness of AAO measured was the highest value around 1.382μm. As general, thickness of AAO film increased as the anodizing temperature increased. Meanwhile, the thickness of AAO also strongly influenced by the concentration of the electrolyte. In 0.5M, the thickness of AAO is 1.403μm and was the highest value. The dielectric properties was measured using impedance analyzer. According to the result, the resistance of AAO film decreased when the anodizing voltage, electrolyte temperature and concentration increased. However, capacitance decreased when the voltage and concentration increased but increased as the temperature increased. Based on the analyzed data, the optimum parameter for anodizing should be in the range 45V ,the anodizing temperature should be at 20oC near room temperature and the electrolyte concentration in the range 0.3M in order to develop the best AAO film with great properties for electronic applications.